Perilaku Menyusui pada Ibu dengan HIV-AIDS di Kota Yogyakarta - Pariawan Lutfi Ghazali; Faizia Maulida (Media Kesehatan Masyarakat Indonesia, 2019)
The World Health Organization (WHO) recommends exclusive breastfeeding for 6 months for children bornto HIV infected mothers who have received ARV therapy. This study aims to determine perceptions, behaviors, andfactors that influence breastfeeding behavior in mothers with HIV-AIDS in Yogyakarta. This study use qualitativeresearch method, with in-depth interviews and observation as data collection methods. Research subjects werebreastfeeding mothers with HIV-AIDS, family, and chaperones. Data validity was tested by source triangulationmethod. Research data were processed using the fixed comparison method. This research shows that breastfeedingmothers with HIV-AIDS in Yogyakarta believes that the process of providing nutrition to infants is the nature of awoman that can not be replaced by anyone. The behavior of breastfeeding mothers with HIV-AIDS in Yogyakartais divided into mothers who provide formula milk, breast milk, and donor breast milk. Factors that influencebreastfeeding behavior of mothers with HIV-AIDS in Yogyakarta, namely internal factors and support from family,chaperones., health workers, and peers. This research concludes that breastfeeding mothers with HIV-AIDS havereasons related to the risk of HIV transmission in deciding breastfeeding behavior.